The User Experience (UX) Analysis of Self-Service Kiosk (SSK) in Waiting Time at Fast Food Restaurant Using User Experience (UX) Model - Abdul Hamid, Nor Aziati (Journal of Social Transformation and Regional Development, 2021)
Studies found that customer satisfaction is affected by customers’ waiting time in fast food restaurants. With the introduction of self-service kiosks (SSK) at McDonald’s, number of complaints about long waiting time has been rising. Hence, this research intends to identify the relationship between user experience (UX), perceived waiting time, and waiting environment towards customer satisfaction. Additionally, this research also determines the relationship between UX and waiting environment towards perceived waiting time as well as to investigate behavioral intention upon customer satisfaction and perceived waiting time. 161 survey questionnaires were collected at McDonald’s Parit Raja. Findings reveal UX and waiting environment affect customer satisfaction, however, perceived waiting time showed no effect to customer satisfaction. While UX and waiting environment affect perceived waiting time, and lastly perceived waiting time and customer satisfaction affect behavioral intention. Nevertheless, sample size of this study was limited and not sufficient to represent the population. Future research should include more areas in Malaysia and adopt mixed research method which compares SSK and queuing system. This paper provides insight for service sector to better understand the determinants of customer satisfaction and behavioral intention after implementing SSK in fast food restaurant.